1999
DOI: 10.1007/s004280050361
|View full text |Cite
|
Sign up to set email alerts
|

Strongly reduced expression of the cell cycle inhibitor p27 in endometrial neoplasia

Abstract: In the present study we investigated the expression of the cell cycle inhibitor p27 in endometrial neoplasia using immunohistochemistry with a p27-specific antibody. Expression of p27 in endometrial carcinomas was compared with expression in the normal endometrium throughout the cycle. Normal endometrial cells showed strong nuclear expression of p27. Expression was present throughout the cycle and was stronger during the secretory phase. We found strongly reduced or abolished expression of p27 in endometrial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
29
1
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 28 publications
5
29
1
3
Order By: Relevance
“…The fact that MT-hGHRH transgenic mice with intact p27 were hyperprolactinemic and had elevated GH and IGF-I levels but normal uterine histologic features suggest that p27 protects endometrial cells from growth factor stimulation (prolactin, IGF-I and/or estrogen). This hypothesis is consistent with the fact that the p27 protein is not detectable in hyperplastic and neoplastic endometrial tissue (Bamberger et al, 1999b) but can be induced by medroxyprogesterone acetate, a treatment that also suppresses endometrial cell proliferation (Shiozawa et al, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…The fact that MT-hGHRH transgenic mice with intact p27 were hyperprolactinemic and had elevated GH and IGF-I levels but normal uterine histologic features suggest that p27 protects endometrial cells from growth factor stimulation (prolactin, IGF-I and/or estrogen). This hypothesis is consistent with the fact that the p27 protein is not detectable in hyperplastic and neoplastic endometrial tissue (Bamberger et al, 1999b) but can be induced by medroxyprogesterone acetate, a treatment that also suppresses endometrial cell proliferation (Shiozawa et al, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…Second, Skp2, the oncogenic subunit of the Skp1/Cul1/F-box protein complex that directs FOXO1 ubiquitination and proteasomal degradation, is overexpressed in EECs (Lahav-Baratz et al, 2004). Third, the expression of known FOXO target genes, such as the cyclin-dependent kinase inhibitor p27 kip , is dramatically lower in malignant endometrium (Bamberger et al, 1999). Moreover, unopposed oestrogen signalling, a well-recognized risk factor for EEC (Amant et al, 2005;Shang, 2006), has been shown to enhance PI3K/Akt activity through binding of oestrogen receptor a (ERa) to the p85a regulatory subunit of PI3K .…”
Section: Discussionmentioning
confidence: 99%
“…In the endometrium, it was reported that p27 was expressed in the secretory phase, but less in the proliferative phase (Shiozawa et al, 1998;Bamberger et al, 1999). Its expression was also higher in endometrial hyperplasia than in the proliferative phase and was significantly increased when the former was treated with medroxyprogesterone acetate (Shiozawa et al, 1998).…”
mentioning
confidence: 99%